Writings of the Luddites - Binfield, Kevin (Johns Hopkins University Press, 2004)
"As mechanization spread through the British cloth industries in the early nineteenth century, skilled textile workers, already suffering because of a generally weak economy, high unemployment, and the weakening of traditional guides, saw their wages and jobs erode further. Earlier efforts to block the introduction of powered machinery through legislation had failed, and in 1811 loosely organized bands of workers, striking most often by night - first in the Midlands, then in Yorkshire and Northwestern England - began destroying the new knitting frames and other equipment. Claiming as their leader the probably mythical Ned Ludd, they became known as Luddites. Although best known for violent action, the Luddite movement also produced a considerable body of writing, from threatening letters, to petitions and proclamations, to poems and songs. In this book, literary scholar Kevin Binfield collects a broad range of complete texts written by Luddites or their sympathizers from 1811 to 1816, adding detailed notes on each and organizing them according to the three major regions of Luddite activity." "To introduce the volume Binfield provides a historical overview of the Luddites, then examines more closely their rhetorical strategies while illuminating the literary contexts of their writings. Ranging from judicious to bloodthirsty in tone, the texts reveal a fascination with legal forms of address and an acute awareness of the recent political revolutions in France and America, and reflect also the more personal forms of Romantic literature. As Adrian Randall of the University of Birmingham concludes in his foreword, this collection of diverse, carefully presented texts clearly demonstrates the significance of Luddite writings within the movement and serves as an important reference for scholars of rhetoric and of the history of labor, technology, and society."--Jacket